Key Determinants of Kano Diaspora’s Shift from Traditional Radio to Online Streaming Platforms: A Descriptive Survey Study - Marmara, Amina Daiyabu; Ibrahim , Adamkolo Muhammed; Ibrahim, Abubakar Tijjani (Feedback International Journal of Communication, 2025)
Radio has historically served as a vital medium for maintaining cultural identity and civic participation among migrants. However, limited research has examined why members of the Kano State diaspora increasingly migrate from analogue FM/AM broadcasting to internet-based radio platforms. Guided by Domestication Theory and a moderated perspective on Technological Determinism, this study employed a structured online questionnaire. The survey targeted 353 adults aged 18–45 from the Kano Diaspora residing in the United States, the United Kingdom, and the United Arab Emirates, all of whom accessed Kano-origin radio stations at least once a month. Descriptive statistics, including percentages and mean scores, were used to analyse demographic profiles and rank six hypothesised motivators: time-shifted access, content variety, participatory features, technological currency, social media integration, and community information services. Findings indicate that flexible listening schedules (80%), opportunities for real-time feedback (74%), and expanded programme choice (70%) were the most significant drivers of digital migration. Additionally, 66% of respondents valued social media integration for sustaining communal discourse, while 62% acknowledged that regular technological updates shaped their listening practices. The study highlights that internet-based radio offers the diaspora greater convenience, interactivity, and programme diversity than analogue broadcasting. It recommends that broadcasters tailor schedules to diaspora time zones, provide simple app-onboarding tutorials, and maintain low-data streaming options. Media educators should design modular digital-literacy programs, while policymakers may consider diaspora-targeted broadband subsidies. These insights advance scholarly debates on transnational media consumption and offer practical guidance for sustaining radio’s relevance in a digitally mediated environment.